2007
DOI: 10.1128/aem.02111-06
|View full text |Cite
|
Sign up to set email alerts
|

Actively Growing Bacteria in the Inland Sea of Japan, Identified by Combined Bromodeoxyuridine Immunocapture and Denaturing Gradient Gel Electrophoresis

Abstract: A fundamental question in microbial oceanography concerns the relationship between prokaryote diversity and biogeochemical function in an ecosystem context. We combined bromodeoxyuridine (BrdU) magnetic bead immunocapture and PCR-denaturing gradient gel electrophoresis (BUMP-DGGE) to examine phylotype-specific growth in natural marine assemblages. We also examined a broad range of marine bacterial isolates to determine their abilities to incorporate BrdU in order to test the validity of the method for applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 65 publications
7
61
0
1
Order By: Relevance
“…Considering that PCR-DGGE bands indicate the predominant community members [18] and that the BrdU-immunocapture technique can detect actively growing bacteria specifically [25], the difference between the total and the BrdU-immunocaptured bacterial community indicated that more than half of the growing bacterial phylotypes were minor populations. The results obtained in this study are similar to those of Hamasaki et al [33] who used the same technique. The low abundance of actively growing bacteria could be caused by the differences in phylotype-specific mortality by viral infection, selective ingestion of actively growing bacteria by heterotrophic nanoflagellates [44,45], and/or UVBR [13,15,46].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Considering that PCR-DGGE bands indicate the predominant community members [18] and that the BrdU-immunocapture technique can detect actively growing bacteria specifically [25], the difference between the total and the BrdU-immunocaptured bacterial community indicated that more than half of the growing bacterial phylotypes were minor populations. The results obtained in this study are similar to those of Hamasaki et al [33] who used the same technique. The low abundance of actively growing bacteria could be caused by the differences in phylotype-specific mortality by viral infection, selective ingestion of actively growing bacteria by heterotrophic nanoflagellates [44,45], and/or UVBR [13,15,46].…”
Section: Discussionsupporting
confidence: 91%
“…This technique has recently been used for quantification of DNA-synthesizing bacteria in seawater [26][27][28][29][30][31]. PCR-DGGE combined with the immunocapturing method succeeded in distinguishing actively growing bacteria from the bacterial community in the ocean [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…We recognise the potential caveats of BrdU incorporation to detect metabolically active microorganisms. There is evidence in fact that a certain fraction of active microbial taxa may be missed because of their intrinsic inability to incorporate BrdU (e.g., Hamasaki et al, 2007). Furthermore, despite the fact that we amended in excess, we cannot exclude that some taxa used metabolites from others.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the possible exception of the high G þ C-containing Actinobacteria, this method has limited application and does not separate bacteria by phylogeny. Combining bromodeoxyuridine immunocapture and DGGE has been proposed to separate the DNA of the actively growing bacteria from the rest of the environmental DNA (Hamasaki et al, 2007). However, this results in the analysis of subgroups of bacteria that are not defined on phylogenetic criteria, and does not allow screening of the whole range of genetic bacterial diversity.…”
Section: Introductionmentioning
confidence: 99%